RFID Tag Helix Antenna Sensors for Wireless Drug Dosage Monitoring - Haiyu Huang; Peisen Zhao; Pai-Yen Chen; Yong Ren; Xuewu Liu; Ferrari, Mauro; Ye Hu; Akinwande, Deji (IEEE journal of translational engineering in health and medicine, 2014)
Miniaturized helix antennas are integrated with drug reservoirs to function as RFID wireless tag sensors for real-time drug dosage monitoring. The general design procedure of this type of biomedical antenna sensors is proposed based on electromagnetic theory and finite element simulation. A cost effective fabrication process is utilized to encapsulate the antenna sensor within a biocompatible package layer using PDMS material, and at the same time form a drug storage or drug delivery unit inside the sensor. The in vitro experiment on two prototypes of antenna sensor-drug reservoir assembly have shown the ability to monitor the drug dosage by tracking antenna resonant frequency shift from 2.4-2.5-GHz ISM band with realized sensitivity of 1.27 μ l/MHz for transdermal drug delivery monitoring and 2.76- μ l/MHz sensitivity for implanted drug delivery monitoring.